2016
DOI: 10.1371/journal.pgen.1006349
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Transporter SLC39A7/ZIP7 Promotes Intestinal Epithelial Self-Renewal by Resolving ER Stress

Abstract: Zinc transporters play a critical role in spatiotemporal regulation of zinc homeostasis. Although disruption of zinc homeostasis has been implicated in disorders such as intestinal inflammation and aberrant epithelial morphology, it is largely unknown which zinc transporters are responsible for the intestinal epithelial homeostasis. Here, we show that Zrt-Irt-like protein (ZIP) transporter ZIP7, which is highly expressed in the intestinal crypt, is essential for intestinal epithelial proliferation. Mice lackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 51 publications
3
90
0
Order By: Relevance
“…The +4 cells are thought to be quiescent cells, whereas CBC cells are actively cycling and are marked by Lgr5 or Olfm4 [17] . We also found that ZIP7 is expressed in active cycling Olfm4 + stem cells indicating that ZIP7 may have an important role in the intestinal self-renewal process [14] .…”
Section: Zip7 Is Expressed In the Intestinal Crypt Where The Intestinmentioning
confidence: 55%
See 3 more Smart Citations
“…The +4 cells are thought to be quiescent cells, whereas CBC cells are actively cycling and are marked by Lgr5 or Olfm4 [17] . We also found that ZIP7 is expressed in active cycling Olfm4 + stem cells indicating that ZIP7 may have an important role in the intestinal self-renewal process [14] .…”
Section: Zip7 Is Expressed In the Intestinal Crypt Where The Intestinmentioning
confidence: 55%
“…We found that ZIP7 was highly expressed in the crypt epithelium than in the villus epithelium [14] . Intestinal crypts are the region where intestinal stem cells are self-renewed and generate TA cells.…”
Section: Zip7 Is Expressed In the Intestinal Crypt Where The Intestinmentioning
confidence: 75%
See 2 more Smart Citations
“…In addition, ZnT5 −/− / ZnT7 −/− cells displayed an exacerbated ER stress response (26). Similarly, KD of Zip7, Zip13, and ZnT3 in cells induced ER stress and higher cell death, indicating the importance of normal zinc homeostasis for ER stress adaptation (27,28,60).…”
Section: Discussionmentioning
confidence: 98%